PENGARUH HARGA DAN PERSEPSI KUALITAS TERHADAP MINAT PEMBELIAN ULANG PADA UMKM PECAH BELAH YENI JAPANG - Candrianto Candrianto; Yeni Arlinda (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
This study aims to determine the effect of prices and perceived quality on the interest in repurchasing Yeni Japang SME. This research is a causative study with quantitative methods. The sample used in this study were 100 respondents. The results showed that the price had a negative but not significant effect on the intention to repurchase Yeni Japang split MSMEs. This means that if the price of a glass plate increases, the interest in repurchasing decreases or vice versa. This product is very sensitive to price changes. Further perceptions of quality have a significant positive effect on repurchase interest. This means that the customer has a high perception of product quality, it will arouse the interest of customers to repurchase. Perception of quality is one of the determinants of whether a customer will buy a product or not.